(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The derivatives with zero-suffix (with meaning of the phenomena of nature and physical phenomena) on the basis of modern Ukrainian language are represented in the article. The author described the derivatives with zero suffix, their semantic and number, their function in comparison with derivatives with others suffixes.